Secondary Traumatic Stress (STS) among Security Forces - Muwafa Falaiyah, Ashraf; Sabet Jaber Alatrany, Saad (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This article aims to examine the prevalence of secondary traumatic stress (STS) among security forces as well as to investigate the difference in STS according to educational level and social state. Methods: (203) participants of security forces were selected from the internal ministry. The Arabic version of the scale of secondary traumatic stress (STS) is used to achieve the study's objects. Results: The results showed that the most common symptoms identified were inability to recall traumatized colleagues' information, followed by cued physiological reaction, irritability, and hypervigilance. However, fewer symptoms experienced were reported in diminished activity level, avoidance of people, places, and things, and emotional numbing. In addition, the results found that females reported more symptoms of STS than males. However, no significant differences were found in STS according to educational level and social state.